Effect of Play Group and Biopsychosocial Factors on the Independence Development of Preschool Children in Surakarta - Marlinawati, Iin Tri; Salimo, Harsono; Murti, Bhisma (Journal of Maternal and Child Health, 2017)
Background: The development of childrens independence is important for their future competitiveness in the rapidly increasing social changes. Disturbance in the development of childrenÃ¢â¬â¢s independence may have a negative future impact in adult life and children become dependent individuals. Efforts are needed to help children develop optimally. Some play groups have been introduced to meet this need in Surakarta, but no studies have been carried out to evaluate its effectiveness. This study aimed to determine the effect of play group on the independence development of preschool children while controlling for the effect of biopsychosocial factors .Subjects and Method: This was an analytic observational study using case control design. The study was conducted at 3 kindergartens in Surakarta, Central Java, from February to April 2017. A sample of 120 kindergarten pupils were selected for this study by purposive sampling and random sampling. The dependent variable was independence development. The independent variables were play group participation status, parenting style (autoritarian, democratic, and permissive), parental education, and child age. The data were collected by a set of questionnaire and analyzed by path analysis.Results: Maternal education Ã¢â°Â¥Senior High School (b= 8.77; 95% CI= 1.89 to 15.65; p= 0.012), paternal education Ã¢â°Â¥Senior High School (b= 9.82; 95% CI = 2.70 to 16.93; p= 0.007), child age Ã¢â°Â¥5 years old (b= 5.59; 95% CI = 1.50 to 9.68; p= 0.007), participation in play group (b= 9.45; 95% CI = 2.19 to 16.71; p= 0.011), and democratic parenting style (b= 0.12; 95% CI= 0.02 to 0.23; p= 0.018) increased child independence. Autoritarian parenting style (b= -0.15; 95% CI= -0.26 to -0.04; p= 0.006) and permissive parenting style (b= -0.09; 95% CI= -0.20 to 0.01; p= 0.092) decreased child independence. Participation in play group was determined by democratic parenting style (b= 0.01; 95% CI -<0.01 to 0.03; p= 0.080), permissive parenting style (b= -0.03; 95% CI -0.05 to <0.01; p= 0.027), paternal education Ã¢â°Â¥Senior High School (b= 2.06; 95% CI= 0.88 to 3.24; p= 0.001), and child age Ã¢â°Â¥5 years old (b= 1.42; 95% CI= 0.63 to 2.21; p <0.001).Conclusion: Maternal education Ã¢â°Â¥Senior High School, paternal education Ã¢â°Â¥Senior High School, child age Ã¢â°Â¥5 years old, participation in play group, and democratic parenting style, positively and directly affect child independence. Autoritarian parenting style and permissive parenting style negatively and directly affect child independence.Keywords: play group, parenting style, biopsychosocial factor, independence, development, preschool childrenCorrespondence:ÃÂ Iin Tri Marlinawati. Masters Program in Public Health, Sebelas Maret University, Jl. Ir. Sutami 36 A, Surakarta, 57126, Central Java, Indonesia. Email: iin3marlina@gmail.com. Mobile: +6285600252256Journal of Maternal and Child Health (2017), 2(4): 284-296https://doi.org/10.26911/thejmch.2017.02.04.01